Human Spirituality: Jean-Louis Chrétien and the Vital Side of Speech - Francesca Peruzzotti (Religions, 2021)
Jean-Louis Chrétien founded his phenomenological enquiry on an analysis of the word as defined by the call and response link. His analysis provides an in-depth approach to spiritual experience as a basis for authentic religious experience. The description of the theoretical sites in which he confronts the theme of the spirit (vital breath, Holy Spirit, inspiration of Scripture, and spiritual life and prayer) determines some fixed points that allow us to define spiritual experience as intersubjective and fleshly, and therefore, not reducible to solipsism and intimism.